STRATEGI PEMASARAN BERDASARKAN PERILAKU PEMBELIAN KERIPIK PISANG DI KOTA METRO - Ine Indriastuti; Muhammad Irfan Affandi; Yaktiworo Indriani (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2015)
The objectives of this research are to analyze dominant factors on the consumer’s buying decision of banana chips and formulate a marketing strategy based on consumer behavior and marketing mix. The research was conducted by a survey method in Sub-district of East Metro of Metro City. This location was chosen on purpose by considerate that  place are crowded which is well known as the central area of the banana chips in Metro.  There were 100 respondents of both men and women that met the inclusion samples’ criteria, such as having at least an experience in buying banana chips.  The results showed that there were three dominant component factors that influenced purchasing decisions of banana chips: the first principal component factor was named as performance (live style) and price product, the second major components was named the shape, and the third major components was named flavour variations of banana chips. Marketing strategy banana chips are utilizing the product prices to improve the image of product for consumers, improving skills and technology, expand the marketing of products to potential region and have never reached a competitor, utilizing local specialty food products as to obtain a large market opportunity and increase the carrying capacity of low funds by utilizing the carrying capacity of the goverment. Key words: banana chips, buying decision, consumer behavior, factor analysis